2023
DOI: 10.1126/science.abo0233
|View full text |Cite
|
Sign up to set email alerts
|

A Neptune-mass exoplanet in close orbit around a very low-mass star challenges formation models

Guðmundur Stefánsson,
Suvrath Mahadevan,
Yamila Miguel
et al.

Abstract: Theories of planet formation predict that low-mass stars should rarely host exoplanets with masses exceeding that of Neptune. We used radial velocity observations to detect a Neptune-mass exoplanet orbiting LHS 3154, a star that is nine times less massive than the Sun. The exoplanet’s orbital period is 3.7 days, and its minimum mass is 13.2 Earth masses. We used simulations to show that the high planet-to-star mass ratio (>3.5 × 10 −3 ) is not an expected outcome of either the core a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…However, we emphasize that such measurements should be done under the same definition of CJs (100 M ⊕ M p 13.6 M J , 1 a 5 au); otherwise, they cannot be directly compared with the results in this work. Ground-based blind RV surveys, notably in the nearinfrared band, definitely provide a pathway to constrain the η CJ around M dwarfs (e.g., Morales et al 2019;Stefansson et al 2023). Microlensing (Mao & Paczynski 1991;Gould & Loeb 1992) and direct imaging (Montet et al 2014;Zhang et al 2021) have also shown their capability in discovering cold giants around M stars, though the detection rates of these two techniques are relatively low.…”
Section: Future Prospectsmentioning
confidence: 99%
“…However, we emphasize that such measurements should be done under the same definition of CJs (100 M ⊕ M p 13.6 M J , 1 a 5 au); otherwise, they cannot be directly compared with the results in this work. Ground-based blind RV surveys, notably in the nearinfrared band, definitely provide a pathway to constrain the η CJ around M dwarfs (e.g., Morales et al 2019;Stefansson et al 2023). Microlensing (Mao & Paczynski 1991;Gould & Loeb 1992) and direct imaging (Montet et al 2014;Zhang et al 2021) have also shown their capability in discovering cold giants around M stars, though the detection rates of these two techniques are relatively low.…”
Section: Future Prospectsmentioning
confidence: 99%
“…The existence of a few giant planets around mid-to late (later than M3) M stars has challenged the core accretion planet formation theory (e.g., Morales et al 2019;Stefánsson et al 2023). Planet population synthesis simulations often fail to form any giant planet around these very low mass stars, in both the planetesimal accretion case (e.g., Miguel et al 2020) and the pebble accretion case (e.g., Liu et al 2019;Burn et al 2021;Mulders et al 2021;Schlecker et al 2022).…”
Section: Introductionmentioning
confidence: 99%